Analisis Daya Dukung Tiang Pancang terhadap Pengaruh Review Design Jembatan Wailola Besar Bula, SBT - Pratama, Gabriel; Talakua, Elisabeth; Latar, Sjafrudin (VISA: Journal of Vision and Ideas, 2024)
In the work to replace the Big Wailola Bridge, several problems were encountered, including changes in the height of the planned and actual abutments. The planned abutment height is 7.20 M high and the realized height is 8.80 M. However, the changes (Design Review) do not change the structure of the pile foundation. And also from the boring results at the location it is known that at a depth of 36 M the SPT only shows the number 32, namely clay soil so that the bearing strength of the pile is determined from the frictional resistance between the pile wall and the surrounding soil (Fraction pile).